2018
DOI: 10.1002/hsr2.50
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet component and mean platelet volume as useful screening markers for myelodysplastic syndrome

Abstract: BackgroundHematologic disorders, including myelodysplastic syndrome (MDS), are difficult to identify in routine hematologic examinations using automated hematology analyzers. However, the practical uses of mean platelet component and mean platelet volume (MPV) measured by these analyzers as screening markers for MDS, remain unclear.MethodsMean platelet component and MPV values were measured in the peripheral blood of patients with MDS, aplastic anemia, idiopathic thrombocytopenic purpura, myeloproliferative ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…This gives us a clue for monitoring patients who show an increase in MPV values more closely during their follow-ups and perhaps preparing them for early stem cell transplantation. The percentage increase through time in the MPV values of the patients regardless of treatment was 2.3% in those who survived and 7.2% in those who died, while the difference between the two groups was not statistically significant [8]. Baba et al, associated RDW with clinical outcomes in MDS patients, and no significant correlation was found between RDW and prognosis in patients with increased blast counts, while a significant relationship was found between increased RDW (≥15.0%) and poor prognosis (p=0.0086) in MDS patients with refractory anemia [10].…”
Section: Original Articlementioning
confidence: 73%
See 2 more Smart Citations
“…This gives us a clue for monitoring patients who show an increase in MPV values more closely during their follow-ups and perhaps preparing them for early stem cell transplantation. The percentage increase through time in the MPV values of the patients regardless of treatment was 2.3% in those who survived and 7.2% in those who died, while the difference between the two groups was not statistically significant [8]. Baba et al, associated RDW with clinical outcomes in MDS patients, and no significant correlation was found between RDW and prognosis in patients with increased blast counts, while a significant relationship was found between increased RDW (≥15.0%) and poor prognosis (p=0.0086) in MDS patients with refractory anemia [10].…”
Section: Original Articlementioning
confidence: 73%
“…A significant difference was observed among the hematological response rates of the groups that were assigned based on their IPSS values (p=0.021), and response rates decreased significantly as risk levels increased. Similarly, In the samples collected from 1304 healthy individuals, the mean MPV was 8.1±1.5 fL, while the mean MPV value was 8.9±2.9 fL in patients with aplastic anemia, 9.7±4.4 fL in ITP patients, and 9.0±2.7 fL in patients with myeloproliferative neoplasms, whereas it was relatively high at 12.0±5.0 fL in MDS patients (p<0.001) [8]. In our study, the MPV values of the patients who showed hematological response did not significantly change through the measurement times (p=0.077).…”
Section: Original Articlementioning
confidence: 84%
See 1 more Smart Citation
“…We know that Sost −/− mice have normal hemoglobin levels (Table S2), indicating no issues with iron; however, iron levels in Sost −/− mice have not been directly quantified to date. The increase in mean platelet volume (MPV) in the blood is usually associated with an increase in platelet production, or destruction of platelets, as seen in myeloproliferative diseases [84][85][86], such as chronic myeloid leukemia (CML), myelofibrosis, and myelodysplastic syndrome (MDS) [87][88][89]. Sost −/− mice displayed no changes in the blood platelet levels (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…We know that Sost -/mice have normal hemoglobin levels (Supplemental Table 2) indicating no issues with iron; however, iron levels in Sost -/mice have not been directly quantified to date. The increase in mean platelet volume (MPV) in the blood is usually associated with an increase in platelet production, or destruction of platelets as seen in myeloproliferative diseases (64)(65)(66) such as chronic myeloid leukemia (CML), myelofibrosis, and myelodysplastic syndrome (MDS) (67)(68)(69). Sost -/mice displayed no changes in the blood platelet levels (data not shown).…”
Section: Discussionmentioning
confidence: 99%